Two memoranda from G. Ranis - Ranis, Gustav (The Philippine Review of Business and Economics, 2018)
The renowned development economist Gustav Ranis (1924-2013) will always be associated with the dual-economy model he developed with John Fei [Fei and Ranis 1961]. In addition, however, Ranis took a special interest in Philippine economic affairs and the direction of policy. In 1973, he led a team of foreign and Filipino economists that produced a highly influential volume popularly known as the ?Ranis Report?, arguing comprehensively for a strategy of labor-intensive export-oriented industrialization and rural development as a development strategy for the country that was then under martial rule. Shortly after the Philippine debt crisis sharpened in 1984 and after the EDSA Revolution of 1986, Ranis returned periodically to the country under the auspices of the U.S. government to provide assessments of the country?s economy as well as to provide policy advice to the new government under President Corazon Aquino. The following are two hitherto unpublished memoranda Ranis produced during that period which the Editors believe yield valuable insights into the history of economic policy-making and political economy. They reflect Ranis?s personal assessment of Philippine economic performance and problems confronted by the post-Marcos government. Of particular interest are Ranis?s views on what he regarded as important structural reforms needed to lay a basis for sustained Philippine growth after the crisis, how the government?s commitment to reforms would likely be affected by multilateral assistance and debt restructuring then being proposed, and the importance of country-ownership of such reforms. The Editors are grateful to Prof. Florian Alburo of the U.P. School of Economics (who was deputy-director general at the National Economic and Development Authority at the time) for providing access to these documents, which were circulated informally during the period among policy makers and academics.